Genetic association of microRNA-146a polymorphisms with the severity of coronary artery lesions in acute myocardial infarction - Toan Hoang Ngo; Chuong Quoc Ho; Son Kim Tran (PLoS ONE, 2025)
Background Polymorphisms situated within the microRNA-146a gene have been extensively reported to fulfill a crucial regulatory function in controlling inflammatory responses and modulating gene expression. More recently, these specific genetic variants have also been implicated in the pathogenesis of coronary artery lesions; nevertheless, the current body of available evidence remains notably sparse. Objectives To investigate the characteristics of the microRNA-146a gene polymorphisms rs2431697, rs57095329, and rs2910164, and their association with the severity of coronary artery lesions. Materials and methods This comparative cross-sectional study included patients with acute myocardial infarction (AMI) and a control group, recruited from two hospitals in Can Tho City, Vietnam, between October 2023 and May 2025. All participants underwent clinical evaluation and coronary angiography. Subsequently, the microRNA-146a gene polymorphisms-rs2431697, rs57095329, and rs2910164-were analyzed using gene sequencing. Results A total of 249 patients were included in the AMI group and 249 in the control group. The mean age of the patient cohort (66.65 ± 10.89 years) was similar to that of the controls (66.67 ± 14.12 years). Analysis of the rs2910164 polymorphism showed a lower frequency of the GG genotype in the AMI group compared with the control group (14.9% vs. 20.9%, p < 0.05), and all three SNPs met Hardy–Weinberg equilibrium criteria. Among patients with AMI, 30.5% had three-vessel coronary artery disease, and severe stenosis (≥90% luminal narrowing) was present in 78.3% of cases. Multivariate analysis demonstrated that the rs2431697 CC + TC genotype (OR = 0.10), the rs2910164 GG + CG genotype (OR = 3.23), diabetes mellitus (OR = 5.14), dyslipidemia (OR = 4.01), smoking (OR = 5.16), NT-proBNP ≥ 300 pg/mL (OR = 8.69), a GRACE score > 140 (OR = 10.82), and a TIMI score > 4 (OR = 6.50) were independent predictors of severe coronary stenosis (p < 0.05). Conclusion Patients with acute myocardial infarction had a lower prevalence of the GG genotype of the rs2910164 polymorphism compared with the control group. The rs2910164 polymorphism of microRNA-146a -particularly genotypes carrying the G allele-along with a history of diabetes mellitus, dyslipidemia, smoking, NT-proBNP ≥ 300 pg/mL, a GRACE score > 140, and a TIMI score > 4 were identified as independent predictors of severe coronary artery stenosis. In contrast, the rs2431697 polymorphism with genotypes carrying the C allele was found to be a protective factor.